Emulsion Ionic Liquid Membrane For Ibuprofen Removal From Synthetic Wastewater Using Aliquat 336 - Rajandram, Logaisri (Universiti Sains Malaysia, 2022)
Ibuprofen (IBP) is one of the non-steroidal anti-inflammatory drugs (NSAIDs) which is classified as an emerging concern and has attracted a huge interest from the researchers around the globe in search of better wastewater separation techniques. Emulsion liquid membrane (ELM) has the potential to treat the IBP presented in the wastewater where this system offers a number of benefits, including easily operated, high selectivity and single stage extraction-stripping process with minimal energy consumption. However, maintaining the stability of the membrane is crucial. Ionic liquid carrier becomes one of the alternative carriers to increase the stability of the system. To formulate an emulsion ionic liquid membrane (EILM), a screening process was carried out to choose a suitable diluent, carrier and stripping agent for the removal of IBP from synthetic wastewater. Sorbitan monooleate, Span 80 was fixed as the surfactant of the membrane throughout the study. The EILM system consisted of hexane (diluent), Aliquat 336 (carrier) and 0.1M Na2CO3 (stripping agent) was the best EILM formulation from the screening process which provided the IBP removal efficiency of about 82.6%. The effects of parameters such as carrier concentration, surfactant concentration, stirring speed and emulsification time were further investigated to obtain the best experimental conditions for the removal of IBP using the formulated EILM system. The best experimental conditions to produce the most stable membrane with the highest IBP removal efficiency was found at 2 wt% of Aliquat 336, 4 wt% of Span 80, 300 rpm of stirring speed and 10 minutes of emulsification time. Hence, the removal efficiency of IBP was improved to 91.3% with 0.016% of membrane breakage. Membrane characterization also was done by capturing the emulsion droplets size of EILM at the best experimental conditions using an optical microscope. Meanwhile, Fourier transform infrared spectroscopy (FTIR) was used to determine the functional groups presented in the membrane phase of the formulated EILM. In short, the formulated EILM has high potential to remove the IBP from synthetic wastewater efficiently with minimal membrane breakage.